2022
DOI: 10.3390/ijerph19084524
|View full text |Cite
|
Sign up to set email alerts
|

Study on Air Quality and Its Annual Fluctuation in China Based on Cluster Analysis

Abstract: Exploring the spatial and temporal distribution characteristics of air quality has become an important topic for the harmonious development of human and nature. Based on the hourly data of CO, O3, NO2, SO2, PM2.5 and PM10 of 1427 air quality monitoring stations in China in 2016, this paper calculated the annual mean and annual standard deviation of six air quality indicators at each station to obtain 12 variables. Self-Organizing Maps (SOM) and K-means clustering algorithms were carried out based on MATLAB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In Lao Cai city, the SO 2 content ranges from 0.009-0.097 mg/m 3 [12], with this result the SO 2 content fluctuates considerably compared to the Southern region. According to Ghorani-Azam and Riahi-Zanjani et al [6] and Zhang and Chen et al [47], SO 2 not only causes harms to human health such as irritation, respiratory dysfunction, exacerbation of cardiovascular disease, eye damage, bronchospasm, but also causes into acid rain, acidifying the soil, affecting soil, forest and freshwater ecosystems. In general, the SO 2 content in the air in the Southern Vietnam study area is still within the allowable limit of QCVN 05:2013/BTNMT (SO 2 , 350 µg/m 3 ).…”
Section: ) Noise Tsp So 2 and Nomentioning
confidence: 99%
See 1 more Smart Citation
“…In Lao Cai city, the SO 2 content ranges from 0.009-0.097 mg/m 3 [12], with this result the SO 2 content fluctuates considerably compared to the Southern region. According to Ghorani-Azam and Riahi-Zanjani et al [6] and Zhang and Chen et al [47], SO 2 not only causes harms to human health such as irritation, respiratory dysfunction, exacerbation of cardiovascular disease, eye damage, bronchospasm, but also causes into acid rain, acidifying the soil, affecting soil, forest and freshwater ecosystems. In general, the SO 2 content in the air in the Southern Vietnam study area is still within the allowable limit of QCVN 05:2013/BTNMT (SO 2 , 350 µg/m 3 ).…”
Section: ) Noise Tsp So 2 and Nomentioning
confidence: 99%
“…Nitrogen dioxide (NO 2 ) is an important ambient air pollutant that can increase the risk of respiratory infections, mainly emitted by motorcycle engines, is a traffic-related air pollutant [6]. According to Zhang and Chen et al [47], NO 2 is an important precursor of anthropogenic ozone and urban smog, and an important factor in the formation of nitric acid, fine particulate matter, and polycyclic aromatic nitro-hydrocarbons. The concentration of NO 2 determined in the study area ranged from 14±2.53-42.38±16.33 µg/m 3 among the types of impacts (Table IV), continuing to be the lowest in the tourist area and the highest in the urban area.…”
Section: ) Noise Tsp So 2 and Nomentioning
confidence: 99%
“…In this study, we defined the 95th and 99th percentile values of daily mean SWSs as extreme SWSs. The extreme value index for wind speed was calculated using a parameter fitting method (Ren et al., 2010; Zhang et al., 2018), and the 95th and 99th percentile values of daily mean wind speeds in a year were obtained using the following formulas: km<pk+1m $\frac{k}{m}< p\le \frac{k+1}{m}$ x(k)<εpx(k+1) ${x}_{(k)}< {\varepsilon }_{p}\le {x}_{(k+1)}$ εp=(normalmnormalpk)()x(k+1)x(k)+x(k) ${\varepsilon }_{p}=(\mathrm{m}\mathrm{p}-k)\left({x}_{(k+1)}-{x}_{(k)}\right)+{x}_{(k)}$ Here, x 1 , x 2 ,⋯, x m is mean wind speed data, x (1) , x (2) ,⋯, x ( m ) is mean wind speed data sorted from small to large, ε p ( p = 95%, p = 99%) is percentile value of daily mean wind speeds. Make the positive integer k ( k = 0,1,⋯, m − 1) satisfy the in equation of and , and then solve the Equation .…”
Section: Methodsmentioning
confidence: 99%
“…In this current study, the concentration of NO2 in the air is still within the limit of QCVN 05:2013/BTNMT. The previous study reported that NO2 is a precursor of anthropogenic ozone and urban smog [54].…”
Section: Air Quality In the Study Areamentioning
confidence: 99%
“…CO results from incomplete fuel combustion in the vehicle engine, and SO2 is generated by heavy-duty diesel engines, buses, and trucks [19,62,63]. NO2 can be formed through the chemical reactions of nitric oxide and other air pollutants, and NO 2 is an important precursor of ozone [54].…”
Section: Table 4 Key Parameters Influencing Air Quality In the Study ...mentioning
confidence: 99%